Software para o dimensionamento de trocadores de calor casco e tubo - Alves, Guilherme Leonhano (2023)
Heat exchangers are widely used devices in various applications for heating or cooling fluids. Among the various existing models of heat exchangers, the focus of this work will be on the shell and tube model, as it is the most used model in industries. The objective of this work is to develop a program for the automation of thermohydraulic design calculations for shell and tube heat exchangers, with a graphical interface that facilitates usability by correlating properties with visual representation. For the development of the code, the Python programming language was chosen due to its versatility, simple syntax, and large community with various libraries available for use. For the thermohydraulic calculations, there are several methods available in the literature, and the selected method for this work is the Bell-Delaware method, which is the most recent and accurate. After the code implementation, tests were conducted using values from other studies to validate the results obtained by the program. The analysis of the results proved to be satisfactory and consistent when compared to other results. With all this in mind, the developed program has shown to be a viable alternative to existing software used by large companies, which are costly and inaccessible to most users.